CHALLENGES IN TEACHING ENGLISH TO NON-LINGUISTIC STUDENTS AND HOW TO DEAL WITH THEM - Кириченко, Тетяна; Рідель, Тетяна (SWorldJournal, 2023)
The research aims to provide an overview of the best practices for teaching English to non-linguistic students. There is a discussion concerning the challenges in teaching English to non-linguistic students and explore ways to overcome them. Teaching Engl